A network approach to characterize the teammates’ interactions on football: A single match analysis - Manuel Clemente, Filipe; Lourenço Martins, Fernando Manuel; Santos Couceiro, Micael; Sousa Mendes, Rui; Figueiredo, António José (Cuadernos de Psicología del Deporte, 2014)
*e aim of this case study was to apply a set of network metrics inorder to characterize the teammates’ cooperation in a football team. *esemetrics were applied in three levels of analysis: i) micro (individual analysis);ii) meso (players’ contribution for the team); and iii) macro (global interactionof the team). One-single case study match was observed and fromsuch procedure were analysed 131 attacking plays. Results from the macroanalysis showed a moderate heterogeneity between teammates, thus suggestingthe emergence of clusters within the team. *e players with highestconnections with their teammates were the right defender, central defenderfrom the left side, defensive mid+elder, right mid+elder and the forwardplayer. Finally, in the micro analysis was observed that right defender, centraldefender, right mid+elder and the forward can be considered the centroidplayers during attacking plays, thus being the most prominent in theattacking building. In sum, the network metrics allowed to characterize theteammates’ interaction during the attacking plays, providing an importantand di<erent information that can be useful for the future of match analysis